EHSENSORI (Edukasi Pencegahan Hipertensi dan Senam Sehat Sore Hari) - Wismaningsih, Endah Retnani; Abbas, Akhmadi; Filiya, Ana Nur; Al Anwar, M.; Primawan, Afan; Maharani, Afnida Putri; Rosyida, Alya; Nurissalma, Maulidiyah; Ardila, Natta; Fahmi, Qoedbudin; Ameliya, Ratna; Heni, Tianna; Fajariya, Ainun Qorif; Ananda, Aulia Rahma; Aini, Qurotul (UPT Penerbitan Universitas Jember, 2023)
Background: Hypertension is one of the diseases that causes premature deaths around the world where blood vessels pressure is very high up to 140 / 90 mmHg or more. Based on the results of the analysis of the situation, it is known that hypertension ranks first on the list of most diseases in the Kecamatan Mojoroto. Only about 32,4 % respondents of Kelurahan Banjarmlati Kota Kediri has regularly check their blood pressure. As a form of community service in an effort to prevent hypertension is an activity called EHSENSORI (Edukasi Pencegahan Hipertensi dan Senam Sehat Sore Hari). The purpose of this activity is to improve the knowledge of hypertension prevention and to perform an exercise as physical activity as a form of hypertension prevention. Method: EHSENSORI was a series of activities consist of Edukasi Pencegahan Hipertensi and Senam Sehat Sore Hari. Edukasi Pencegahan Hipertensi is carried out through health counseling by method of lectures with media posters and power points. Senam Sehat Sore Hari is carried out by inviting targets to do exeersice as a form of physical activity..Hypertension prevention evaluation is performed through charging pretest and posttest questionnaires by target, while a healthy afternoon exercise is performed through observation of target enthusiasm during exercise. Results: Through EHSENSORI, the knowledge on the prevention of hypertension can be increased according to the results of pre-test and post-test where the target with high knowledge increased by 86.67%. In addition, the target was very enthusiastic when performing exercise, so the exercise was well perform by the target during the implementation of the community service. Conclusion: Through community service activities EHSENSORI, the knowledge on the prevention of hypertension increased as well as an enthusiastic target during exercise as a form of physical activity in preventing hypertension.Keywords: Hypertension, education, prevention, exercise.